Harmony in Diversity in Border Areas: Dayak Iban Tribe and Migrants in Badau - I Nyoman Yoga Segara; Kustini Kustini; Mustolehudin Mustolehudin; Siti Muawanah; R. Adang Nofandi (El Harakah)
This study aimed to highlight the harmonious coexistence among different ethnic and religious groups. The study was conducted in Badau, a sub-district in West Kalimantan, inhabited by the indigenous Dayak Iban ethnic group and migrants from various ethnic and religious backgrounds. The primary motivation for examining the socio-cultural and religious life in Badau stems from the region's challenges, including limited religious guidance and services, the establishment of places of worship, the roles of traditional and religious leaders, and interfaith relationships. Using a qualitative approach with observation, interviews, and document analysis, the research revealed several key findings. Firstly, customary rules play a significant role in the lives of the Dayak Iban, serving as a guiding principle. They adhere to these rules strictly but with flexibility. Secondly, community leaders and social institutions are instrumental in resolving social issues. The rumah panjang and balai adat are two key mechanisms for conflict resolution. The study recommends conducting anthropological and historical research to trace the origins of the Dayak Iban tribe and explore religious encounters in the region. It also suggests that local governments in border areas emulate Badau’s community resilience, where the Cross-Border Post (PLBN) serves as a living symbol of unity, promoting nationalism and harmony among diverse ethnic, cultural, and religious groups.